Pengaruh Media Smartopoly Pai Dalam Meningkatkan Kemampuan Berpikir Reflektif Siswa Kelas VII Di SMP Insan Cendekia Tuban - Karismatul Maimunah (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2026)
This study began with the issue of students' reflective thinking skills, which are still not optimal in the Islamic Religious Education (IRE) learning process, as seen from their difficulty in examining religious issues in depth, critically assessing various actions, and reflecting on the experiences gained during learning. The main focus of this study was to examine the effect of the SMARTOPOLY (Smart Reflective Topology Learning) learning media, an educational game that adopts the concept of snakes and ladders to encourage reflection, on developing students' reflective thinking skills. The approach used was a pra-experiment with a single pretest-posttest group model, involving 15 students as research subjects. Data were obtained from reflective thinking ability test scores, which were administered before and after the media was implemented. The research findings revealed a significant increase in students' reflective thinking skills after using the SMARTOPOLY media. The average score on the pretest was 64.33, which then jumped to 82.47 on the posttest. Hypothesis analysis using a paired sample t-test produced a Sig. (2-tailed) value of 0.000, which is lower than 0.05, thus indicating a significant difference between the pretest and posttest results. Meanwhile, the N-Gain calculation showed an average of 0.5108 (in the moderate category), which indicates that the SMARTOPOLY media has a sufficient level of effectiveness to improveKeyword: SMARTOPOLY, Reflective Thinking Skills, Learning Media, Islamic Education, Educational Games.